Kajian Pemanfaatan Pupuk Organik Rumput Laut Terhadap Produksi Dua Varietas Bayam (Amaranthus sp.) - Putra Hidayat Telaumbanua; Betzy Victor Telaumbanua; Natalia Kristiani Lase; Januari Dawolo; Ridho Victory Nazara (Paspalum: Jurnal Ilmiah Pertanian, 2023)
Spinach is one of the most important needs for humans, but spinach production in Indonesia has decreased from year to year, so it needs improvement in terms of cultivation technology. The purpose of this study was to analyze the interaction between varieties of spinach and the dose of organic seaweed fertilizer on spinach production; analyzed the dose of organic seaweed fertilizer on spinach production and analyzed the effect of spinach varieties on spinach production. This study was arranged in a factorial randomized block design (RBD), which consisted of two factors, the first factor was the variety of spinach (b) which consisted of two levels, namely green spinach variety Giti Hijau (b1) and red spinach variety Giti Merah (b2), the second factor is the dose of organic fertilizer (d) which consists of 4 levels, namely control (d0), 2 mL/L water (d1), 3 mL/L water (d2), 4 mL/L water (d3). The treatment was divided into 3 blocks as repetition. Data analysis used ANOVA and follow-up test with a DMRT level of 5%. The results showed that the variety of spinach had a significant effect on plant height from 3 to 5 WAP, the number of leaves at 2 WAP and 3 WAP, and the fresh weight of spinach. Fertilizer dosage did not significantly affect plant height, number of leaves, root length, fresh weight, and dry weight of plants . There was no interaction between spinach varieties and doses of organic seaweed fertilizer on all growth parameters and production of spinach.Â